2013
DOI: 10.5761/atcs.oa.12.01994
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative High N-Terminal pro-B-Type Natriuretic Peptide Level Can Predict the Incidence of Postoperative Atrial Fibrillation Following Off-Pump Coronary Artery Bypass Grafting

Abstract: Objective: N-terminal pro-B type natriuretic peptide (NT-pro-BNP) is one of the biomarkers, increased by myocardial ischemia or subsequent, burdened wall stress. The aim of this study was to assess if NT-pro-BNP can predict the incidence of atrial fibrillation (AF) after off-pump coronary artery bypass grafting (OPCAB). Methods: NT-pro-BNP was measured preoperatively in 100 OPCAB patients without preoperative AF. Patients were divided into the AF group (n = 36) of those who developed postoperative AF, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Patients who had high levels of perioperative BNP preserved low levels of LVEF. The ROC curve also revealed that perioperative BNP is a good predictor for cardiac function of patients undergoing on-pump coronary artery bypass graft surgery on a beating heart, which was consistent with the results from Matsuura et al 21 The sample size in this research is small, and the mechanisms of perioperative BNP on cardiac function in patients with CABG is complex, hence a further research with larger sample size would be needed.…”
Section: Discussionsupporting
confidence: 89%
“…Patients who had high levels of perioperative BNP preserved low levels of LVEF. The ROC curve also revealed that perioperative BNP is a good predictor for cardiac function of patients undergoing on-pump coronary artery bypass graft surgery on a beating heart, which was consistent with the results from Matsuura et al 21 The sample size in this research is small, and the mechanisms of perioperative BNP on cardiac function in patients with CABG is complex, hence a further research with larger sample size would be needed.…”
Section: Discussionsupporting
confidence: 89%
“…8,13,16,19,21,33,41,42,44,5563 Other variables, including gender and smoking status, did not demonstrate significant correlation with POAF incidence. 5,7,913,16,1921,26,27,29,30,32,34,35,37,42,44,45,48,49,51,5558,64…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative inflammatory markers such as white cell count, c-reactive protein (CRP), mean platelet volume, soluble receptor activator of nuclear factor-kB and interleukin-2 (IL-2) were found to be associated with POAF in a few small studies but either have not been extensively studied or show conflicting evidence. 13,15,20,34,59,62,72,92,9496,105,112…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aynı zamanda çalışan kalpte koroner baypas serilerinde postoperatif AF oranlarının da daha düşük olduğu rapor edilmiştir (14,15) . Bizim çalışmamızda gruplar arasında, çalışan kalpte ve kardiyopulmoner baypas ile yapılan koroner cerrahi yönünden, AF gelişimi açısından anlamlı istatistiksel fark saptanmadı.…”
Section: Discussionunclassified